Uncovering the Magnetic Particle Imaging and Magnetic Resonance Imaging Features of Iron Oxide Nanocube Clusters - Sahitya Kumar Avugadda; Sameera Wickramasinghe; Dina Niculaes; Minseon Ju; Aidin Lak; Niccolò Silvestri; Simone Nitti; Ipsita Roy; Anna Cristina S. Samia; Teresa Pellegrino (Nanomaterials, 2020)
Multifunctional imaging nanoprobes continue to garner strong interest for their great potential in the detection and monitoring of cancer. In this study, we investigate a series of spatially arranged iron oxide nanocube-based clusters (i.e., chain-like dimer/trimer, centrosymmetric clusters, and enzymatically cleavable two-dimensional clusters) as magnetic particle imaging and magnetic resonance imaging probes. Our findings demonstrate that the short nanocube chain assemblies exhibit remarkable magnetic particle imaging signal enhancement with respect to the individually dispersed or the centrosymmetric cluster analogues. This result can be attributed to the beneficial uniaxial magnetic dipolar coupling occurring in the chain-like nanocube assembly. Moreover, we could effectively synthesize enzymatically cleavable two-dimensional nanocube clusters, which upon exposure to a lytic enzyme, exhibit a progressive increase in magnetic particle imaging signal at well-defined incubation time points. The increase in magnetic particle imaging signal can be used to trace the disassembly of the large planar clusters into smaller nanocube chains by enzymatic polymer degradation. These studies demonstrate that chain-like assemblies of iron oxide nanocubes offer the best spatial arrangement to improve magnetic particle imaging signals. In addition, the nanocube clusters synthesized in this study also show remarkable transverse magnetic resonance imaging relaxation signals. These nanoprobes, previously showcased for their outstanding heat performance in magnetic hyperthermia applications, have great potential as dual imaging probes and could be employed to improve the tumor thermo-therapeutic efficacy, while offering a readable magnetic signal for image mapping of material disassemblies at tumor sites.